The Effect of Cashless Lifestyle on the Consumption Behavior of Generation Z - Nazla Annindya Renanta; Rahma Ardiyanti; Faiza Nur Muthmainah; Marcha Dwi Yuliana (International Journal Administration, Business & Organization, 2026)
Digital payment systems are now a necessary component of Generation Z's everyday lives. The use of e-wallets, QRIS, and mobile banking for a variety of purposes has been boosted by convenience, quick payment processes, and promotional offers such as discounts and cashback. However, as people's capacity to manage their money and exercise self-control also affects their purchasing selections, similar conveniences do not always result in the same consuming behavior. The purpose of this study is to assess the impact of a cashless lifestyle on the consumption habits of Generation Z and investigate the moderating effects of self-control and financial literacy in this context. A total of 201 members of Generation Z who use digital payment systems were surveyed as part of this study's quantitative methodology. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS was used to analyze the data. The findings show that a cashless lifestyle has no discernible impact on consumer behavior. Spending behavior is significantly affected by financial literacy and self-control, which also moderate the association between a cashless lifestyle and spending behavior. These results imply that the extent of digital payment use has less impact on Generation Z's consumption behavior than financial management skills and self-control.